2008
DOI: 10.3346/jkms.2008.23.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PSEN1 and APP Gene Mutations in Korean Patients with Early-Onset Alzheimer's Disease

Abstract: Although mutations in three genes, amyloid precursor protein (APP), presenilin 1 (PSEN1), and presenilin 2 (PSEN2), have been identified as genetic causes of early-onset Alzheimer's disease (EOAD), there has been a single report on a PSEN1 mutation in Koreans. In the present study, we performed a genetic analysis of six Korean patients with EOAD. Direct sequencing analysis of the APP, PSEN1 and PSEN2 genes revealed two different mutations of the PSEN1 gene (G206S and M233T) and one mutation of the APP gene (V7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…An AO of 58 years had been suggested as a cutoff point for genetic analysis based on Western data 9,23. AO was 31, 35, and 34 years in EOAD subjects with genetic mutation, and 62- and 55-year-old patients with AO did not carry causative mutations in a prior Korean study 28. Similarly, AO was 38, 37, and 54 years in our EOAD patients with causative mutation.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…An AO of 58 years had been suggested as a cutoff point for genetic analysis based on Western data 9,23. AO was 31, 35, and 34 years in EOAD subjects with genetic mutation, and 62- and 55-year-old patients with AO did not carry causative mutations in a prior Korean study 28. Similarly, AO was 38, 37, and 54 years in our EOAD patients with causative mutation.…”
Section: Discussionsupporting
confidence: 54%
“…In 2008, Park et al published a genetic screening study, but they employed only 6 EOAD patients. PSEN1 G206S and M233T and APP V715M causative mutations were found in 3 unrelated patients including 1 without family history 28. In 2010, Kim et al published a study on PSEN1 M139I in a family with EOAD 29.…”
Section: Discussionmentioning
confidence: 99%
“…It was confirmed by Sanger sequencing, which revealed 8 carriers of the p.M233T among family members ( Figure 1a ). This pathogenic mutation was reported in several early onset AD families (Campion, et al, 1999,Guerreiro, et al, 2010, Kwok, et al,1997, Park, et al,2008, Raux, et al, 2005). …”
Section: Resultsmentioning
confidence: 75%
“…Previous studies have shown several APP and PSEN1 mutations in Asian populations, but pathogenic PSEN2 mutation has not yet been described [3,4]. We had screened PSEN2 mutation in 90 AD patients of two memory clinics from May to December 2012.…”
Section: Introductionmentioning
confidence: 99%